Bravely - Stiefvater, Maggie, 1981- (Disney Press, 2022)
When a supernatural being appears in DunBroch on Christmas Eve with the intent of demolishing the realm, Princess Merida, under the watchful eyes of the gods, embarks on a series of epic journeys to save those she loves from ruin.